دور جزيرة جربة الإقتصادي بين القرنين الخامس والتاسع هـ - حسن, محمد (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Commerce – Djerba

L'Arabe du coin et le Chinois du quartier, ou le commerce "ethnique" au service de tous - Barou, Jacques (Hommes et Migrations, 1999)
Depuis ceux que l'on a appelés les "Auvergnats de Paris" jusqu'aux restaurants chinois de nos quartiers en passant par l'épicerie berbère du coin c'est selon un même processus qu'à différentes époques , des migrants d'origines diverses exercent leur activité dans le commerce de proximité, là où le lien familial et communautaire tient une place prépondérante. Ce faisant ces commerces contribuent au maintien de la convivialité dans les espaces urbains.
Keywords: Commerce – Djerba

Du colportage à la boutique. Les commerçants maghrébins en France - Kerrou, Mohamed (Hommes & Migrations, 1987)
Keywords: Commerce – Djerba

Mise en scène des commerces maghrébins parisiens - Raulin, Anne (Terrain. Anthropologie & sciences humaines, 1986)
Dans le cadre d'une recherche menée sur les commerces dits ethniques dans le xiiie arrondissement à Paris — principalement asiatiques et maghrébins — une dimension tout à fait particulière de l'activité commerciale nous a paru intéressante à étudier : les signes de « présentation de soi » de l'établissement, sa mise en scène propre. Il convient dans un premier temps de préciser les caractéristiques du cadre dans lequel s'effectue l'analyse. Le commerce dit ethnique — dont la définition même p...
ISBN: 9782110889119 Number: 7
Keywords: Commerce – Djerba

Tunisi - Svezia 23 Dicembre 1736: Trattato di pace e di Commercio (Trattati, convenzioni e accordi relativi all'Africa: 1648-1799, 1940)
Keywords: Commerce – Djerba; Commerce – Zouara; Relations – Tunisie – suède

The Djerbian Ethic: Correlates of the Spirit of Capitalism in Tunisia - Stone, Russell A. (1971)
Keywords: Commerce – Djerba

Les Djerbiens épiciers et polyglottes (Le cri du peuple, 1943)
Keywords: Commerce – Djerba

Révocation de procuration (L'Écho d'Alger, 1939)
Ali Doghri (Aïn Beida) révoque Hadj Ahmed Azzabi
Keywords: Commerce – Djerba

Succession and Social Change in Tunisia - Ashford, Douglas E (International Journal of Middle East Studies, 1973)
Keywords: Commerce – Djerba

Les Jerbiens en Tunisie. Réminiscences d’un sociologue allemand devant une recherche inachevée - Freund, Wolfgang Slim (Revue de l'Institut des Belles Lettres Arabes, 1986)
Abstract (p. 57): departing from his book of 1970, the author explains the reasons that made him doubt the validity of Weber’s sociological models and categories for understanding the economic success of Jerban (and Mīzābī) merchants. In a second part of his article the author indicates guidelines for a more objective sociological understanding of the Jerban phenomenon.
Keywords: Commerce – Djerba

La réussite des Ibadites: le commerce comme exemple - Smaali, Nasr-Eddine (Université Paris 8, 1998)
Keywords: Commerce – Djerba

Religious Ethic and the Spirit of Capitalism in Tunisia - Stone, Russell A. (International Journal of Middle East Studies, 1974)
The relationship between religion and entrepreneurial activity has been an ongoing subject of sociological interest since Weber (1958) first identified the association between Protestantism and the rise of capitalism in Western Europe. One recent collection of papers on the subject (Eisenstadt, 1968) indicates that the topic remains highly controversial, and that the debate moves in two general directions. Some analysts challenge (or support) the factual and/or theoretical validity of Weber's analysis as it applies to Western Europe, or to Protestantism (Green, 1959). Another branch of research attempts to apply the idea on a different level, finding other religious groups for which the theory is valid, in other parts of the world. Most such studies have been made in East and Southeast Asia, but there is a scattering of articles on other countries as well (Eisenstadt, 1968). Bellah (1963) cites several studies of merchant groups in Asia which conform to the Protestant ethic pattern, but points out that they seldom transform the norms of the whole society as Protestantism did in parts of Europe. Their impact is limited to a subgroup within society. These studies suggest that the Weberian thesis might apply on an intra-societal level in cultures different from Europe. The present study attempts to support this idea by positing a relationship between religious ethic and capitalism among a group of merchants in Tunisia who are members of a distinct religious sect within Islam.
Keywords: Commerce – Djerba

Les Djerbiens, des migrants séculaires - Tmarzizet, Kamel (Confluences, 1993)
Keywords: Commerce – Djerba; Emigration – Djerba

Cocuville - Charlerois, André (1961)
Keywords: Commerce – Djerba

Les entrepreneurs djerbiens - Jedidi-Lamandé, Anne-Marie (EHESS, 1994)
Keywords: Commerce – Djerba

Deux documents d'archives relatifs au commerce de Djerba et de Sfax avec l'Egypte au début du XIXe siècle - Zouari, Ali (Revue de l'Occident musulman et de la Méditerranée, 1985)
Discussion and translation of two documents concerning a commercial association between ʿAlī b. Taʿzayt al-Jarbī and Maḥfūẓ Maqnī al-Ṣfāqisī. ʿAlī b. Taʿzayt al-Jarbī, who was originally from Ṣidghiyān or al-Māy at Jerba, where the family still lives today, was active in trade between Egypt and Turkey. He finally had settled in Alexandria. The letter he wrote to his partner in trade was dated 3 Ṣafar 1221/23 April 1806.
Keywords: Commerce – Djerba

La vente à la criée et le crieur public dans les souks tunisois - Glasman, Wladimir (Université d'Aix-Marseille I, 1984)
Keywords: Commerce – Djerba